(untitled) (Altre Modernità, 2021)
The present work tries to approach the figure of the testimony in the case of the so-called second generation in Argentina. That is, the one that includes the sons and daughters of detainees who disappeared during the last military dictatorship, their own traumatic experience, the memory built from that experience and the collection of other objects of history (photographs, anecdotes, books, documents , clothes). These accounts call into question the classic model of the surviving witness’s testimony. They are assembled from precarious images, incomplete memories, all pieces of a puzzle that is explicitly exhibited to account for its form of construction and the purpose of its objective: justice. The incorporation of these testimonies in the so-called trials against humanity in Argentina represents a novelty with respect to similar processes developed in the past (trial of the boards, trials for the truth). On the one hand, contributing from the subjective to the reaffirmation of identity in each one of those sons and daughters who manage to rescue the meaning before the elaboration of the testimony. And on the other, on a more social and collective level, serving as evidence in trials, about kidnapping, torture and disappearance. These two elements are intended to investigate their new configurations and implications.